Improved analytical method for evaluating the responses of a shield tunnel to adjacent excavations and its application. (April 2020) - Liu, Jianwen; Shi, Chenghua; Lei, Mingfeng; Cao, Chengyong; Lin, Yuexiang
Highlights: An improved analytical method for evaluating the responses of shield tunnel due to adjacent excavation is proposed. The proposed method is verified by three case histories. The verified method is applied to a practical project, construction optimization is also performed. A series of parametric analyses are conducted. Abstract: Adjacent excavations may adversely impact existing shield tunnels. Therefore, evaluating the induced responses of existing tunnels is critical. Previous analytical methods have generally treated shield tunnels as Euler–Bernoulli or Timoshenko beams resting on Winkler or Pasternak foundations to simulate tunnel–soil interactions. However, these methods do not consider excavation–induced disturbance to the surrounding soil and lack sufficient theoretical bases for determining subgrade parameters. This study proposes an improved analytical method that utilizes a Timoshenko beam to simulate a shield tunnel, and that considers the bending and shearing effects on a tunnel. The Vlazov foundation model is introduced to simulate tunnel–soil interactions and to further consider induced disturbance to the surrounding soil. The consistency between the measurements obtained from three case histories and the predictions verifies the proposed method. Then, the verified method is applied to a practical project. Results indicate that the predictions are generally consistent with the in situ measurements. Construction optimizations are also performed to meet the safety requirements and to expedite the construction progress. Finally, parametric analyses are conducted, and their results reveal that the factors, including excavation–tunnel relative distance, ground Young's modulus and tunnel buried depth, exert considerable influences on the underlying shield tunnel.